Struktur, Isi, dan Kebahasaan Teks Posedur Siswa Kelas VII SMP Negeri 1 Sutera - Alvionita, Mutiara; Anggraini, Dewi (Journal of Education Language and Innovation, 2023)
The purpose of this research is to describe the structure, to describe the contents, and to describe the language of procedure text for seventh-grade students of SMP Negeri 1 Sutera. This research applied qualitative with descriptive methods. The source of the data is written procedure text for seventh-grade students of SMP Negeri 1 Sutera. The data are collected through documentation studies. The data validation technique in this study is a triangulation technique (cross-check). The data were analyzed based on the aspects of structure, content, and linguistics of the procedure text. The results of the study concluded as follows. First, all the procedure texts have titles, only 23 have objectives, all 30 texts have tools or materials and steps, and on the closing part, students were not able to write a good closing of a procedure text. Second, in terms of content, it was found that there are 20 complete procedure texts and 10 incomplete procedure texts. Third, there are 113 appropriate imperative and 45 inappropriate imperative sentences, 63 correct adverbs, and 3 incorrect adverbs, and there are 385 correct conjunctions and 19 incorrect conjunctions.